2007
DOI: 10.1007/s11055-007-0024-5
|View full text |Cite
|
Sign up to set email alerts
|

Spectral EEG characteristics during increases in the complexity of the context of cognitive activity

Abstract: The spatial and frequency characteristics of cortical electrical activity were studied in healthy human subjects in two series of experiments involving solution of sequentially presented visual tasks. The first task was to assess the relative sizes of two circles and was identical in both series. In the first series, this was supplemented by a task consisting of recognition of pseudowords/words, presumptively also requiring predominant involvement of the ventral "what?" visual system. In the second series, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…Recently, however, proofs of quite another type appear. An increase in the δ SP began to be correlated with increased mental strain, readiness for adequate reactions to certain stimuli, suppression of perception of irrelevant influences, and formation of a goal for cognitive activity [17]. It should be mentioned that a rather clearly expressed δ rhythm in EEGs recorded in the state of functional resting was readily observed in most healthy adult subjects in both our own studies [12] and studies of many other authors [1].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Recently, however, proofs of quite another type appear. An increase in the δ SP began to be correlated with increased mental strain, readiness for adequate reactions to certain stimuli, suppression of perception of irrelevant influences, and formation of a goal for cognitive activity [17]. It should be mentioned that a rather clearly expressed δ rhythm in EEGs recorded in the state of functional resting was readily observed in most healthy adult subjects in both our own studies [12] and studies of many other authors [1].…”
Section: Discussionsupporting
confidence: 68%
“…A rise in the δ rhythm in the frontal cortex was found after receiving an instruction disposing the subject to an activity of the certain type [17]. An increase in the proportion of the δ component was observed in the course of effective processing of visual information [26].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, such modulation of δ oscillations can be related to the readiness for an adequate reaction to presentation of one instructiondetermined stimulus or another [12]. Intensification of δ oscillations can coincide with the acceptance of a decision for a reaction, i.e., with a stage of formation of the aim in the course of intense cognitive activity [13]. Our tests demonstrated that the intense θ-rhythm SP was manifested in the subgroups with a medium N-Ach level and high estimates of the AchM.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is observed in the course of formation of behavioral automated acts and suppression of the trend toward erroneous reactions into the activating cerebral system [8]. Relatively high SPs of the δ rhythm are also related to increased mental stress, readiness for adequate reactions to certain stimuli, inhibition of perception of irrelevant influences, and formation of orientation for cognitive activity [9]. As was mentioned, a relatively high power of δ oscillations was observed in the frontal cortical regions of low-anxiety subjects after closing the eyes [10].…”
Section: Discussionmentioning
confidence: 99%